2016
DOI: 10.1080/02705060.2016.1141379
|View full text |Cite
|
Sign up to set email alerts
|

Differences in life history characteristics among three sympatric evolutionary species of theRotaria rotatoriacomplex

Abstract: The Bdelloidea rotifer, a kind of asexually microscopic invertebrate, is the largest Metazoan group that reproduces only through parthenogenesis. Here the potential evolutionary species composition was analyzed using a coalescent approach to infer independently evolving entities from a phylogenetic tree obtained from cytochrome oxidase I sequences. Three clones (HX4, HX8 and HX19) of Bdelloidea Rotaria rotatoria were selected to be the representatives of three sympatric putative cryptic taxa for detecting the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 66 publications
1
2
0
Order By: Relevance
“…In both species we found a profound effect of temperature on survival; in both species increasing temperature led to reduced life span. Our results corroborate studies in other rotifer taxa that showed a profound effect of temperature on survival (Kauler & Enesco, 2011;Li et al, 2010;Xiang, Jiang, Tao, Chen, & Xi, 2016;. Due to their ectothermic nature, rotifer body temperature increases with increasing ambient temperature, which accelerates metabolic rates.…”
Section: Life History Heat Response Between Heat-tolerant and Heat-sensitive Brachionus Speciessupporting
confidence: 90%
“…In both species we found a profound effect of temperature on survival; in both species increasing temperature led to reduced life span. Our results corroborate studies in other rotifer taxa that showed a profound effect of temperature on survival (Kauler & Enesco, 2011;Li et al, 2010;Xiang, Jiang, Tao, Chen, & Xi, 2016;. Due to their ectothermic nature, rotifer body temperature increases with increasing ambient temperature, which accelerates metabolic rates.…”
Section: Life History Heat Response Between Heat-tolerant and Heat-sensitive Brachionus Speciessupporting
confidence: 90%
“…In the second case, several reports show that there are several degrees of tolerance to desiccation among bdelloid morphospecies (Eyres et al, 2015) but none have focused on variations within species complexes. However, three cryptic species morphologically identified as Rotaria rotatoria have been reported to have distinct temperature preferences (Xiang et al , 2016), often linked to desiccation tolerance. In the present study, we did not identify physico-chemical parameters that may vary among the different dishes.…”
Section: Discussionmentioning
confidence: 99%
“…It was semi-continuously cultivated at 28°C under illumination of 54 μmol•photons m −2 •s −1 and light cycle of Light:Dark = 12 h:12 h. Subsequently, the algae were maintained in the exponential phase by routine dilution using BG-11 medium (Andersen 2005). The rotifer R. rotatoria was sampled from a pond in Hexian, Anhui Province, China, which has been identified by molecular methods in the study by Xiang et al (2016) and microscopic discrimination of morphological characteristics following guidelines from the literature (Donner 1965;Ricci and Melone 2000;Fontaneto et al 2007). The rotifers were subsequently cultured in an 8 mL tumbler with EPA medium (OECD 2004) at 28°C.…”
Section: Cultivation Of the Test Organismsmentioning
confidence: 99%